Epicardial Atrial Fibrillation Ablation and Left Atrial Appendage Amputation in a Patient with Congenital Bicuspid Aortic Valve and Catheter-Induced Cardiac Tamponade - Shi,Yaming (2020)
Abstract Early recognition and rapid and appropriate treatment of cardiac tamponade are mandatory to prevent the irreversible deterioration of cerebral perfusion and other important organs. In this study, cardiac tamponade was induced by inadvertent transseptal puncture, which was managed with pericardial drainage and surgical repair in a patient with symptomatic paroxysmal atrial fibrillation. Epicardial atrial fibrillation ablation and left atrial appendage amputation were also performed at the same time.